Viral aetiology of diarrhoea in puppies from a same shelter in Turkey: presence of mixed infections - Sahna, K. Can; Gencay, A.; Atalay, O. (Ecole Nationale Veterinaire Toulouse, 2008)
This study was conducted to evaluate the prevalence of viral agents that cause enteritis in puppies. Prevalences of canine distemper virus (CDV), canine parvovirus (CPV) and canine rotavirus (CRV) were established using RT-PCR, PCR and polyacrylamide gel electrophoresis (PAGE) techniques respectively, in faecal samples from 1 to 2-month-old diarrheic puppies (n = 34) stemming from a same shelter. Twenty-nine samples (85.3%) were found positive for at least one enteritis virus: the prevalences of CDV and CPV infections were 44.1% and 76.5% respectively while no CRV was evidenced in any sample tested. On the other hand, 12 samples (35.3%) were positive for both CDV and CPV infections. These results demonstrate that the prevalence of viral infections in diarrheic puppies is strong and also that CDV and CPV infections, which may be simultaneously present with a high rate, should not be under-estimated particularly in shelters with a high animal population.
Keywords: CDV; CPV; CRV; mixed infection; PCR; PAGE